Landscapes of power: the cultural and historical geographies of renewable energy in Britain since the 1870's - Gardner, Zoë (2008)
This thesis considers historical applications of naturally renewing energy resources in Britain from the beginnings of public electricity supply in the late nineteenth century to the period immediately prior to the first State interest in such technology in the early 1980s when it became conceptualised as 'renewable'. After a comprehensive review of twentieth century engagements with renewable energy and the academic literatures pertaining to 'water, engineering and landscape' the thesis focuses on two distinct case studies. The first charts the technological, cultural and political evolution of hydro-electricity for public supply which developed over the course of the nineteenth century and was instituted from the 1870s. Detailed consideration of the Worcester hydroelectric station reveals that the development of hydro-electricity in the late nineteenth century symbolised a wider social and cultural demand for 'civic improvement’, and highlights the nature of water as a contested resource within late-Victorian civic arenas. The second traces the history of the Centre for Alternative Technology (CAT), a practical demonstration of alternative energy technologies established in rural mid-Wales during the early 1970s. In a discussion centred on 'alternativeness', the exploration of alternative energy technologies in the early 1970s was the preserve of an emerging counter-culture which sought to implement new visions of Environment and Society. Having revealed these hitherto dormant histories, the thesis concludes with a comparative discussion of the two case studies reflecting on these respective renewable energy projects and their uses as instruments of ‘modernisation' and attempts to extract the significance of these histories in the context of current discourses of renewable energy.